Identificação morfológica de organismos semelhantes à anaplasmataceae em monócitos de surubim híbrido (Pseudoplatystoma reticulatum x P. corruscans) – relato de caso - Ishikawa, Marcia Mayumi; de Padua, Santiago Benites [UNESP]; Satake, Fabiana; Martins, Mauricio Laterca; Dias, Marcos Tavares (Soc Medicina Veterinaria Estado Rio de Janeiro, 2011)
The aim of this study was to report the occurrence of Anaplasmataceae-like organisms in monocytes from the hybrid surubim catfish. During the hematological evaluation of fish infected by Pseudomonas sp. in a fish farm located in the State of Mato Grosso do Sul we observed into the monocytes the presence of numerous pleomorphic inclusions of various sizes, rough in appearance which presented basophilic staining. These inclusions were similar to elementary bodies, initial bodies and morule of the bacteria from Anaplasmataceae family, often diagnosed in domestic mammals. This is the first report of its occurrence possibly belonging to the family of Anaplasmataceae in cultured fish in Brazil. Additional studies are necessary for molecular characterization of this bacteria, pathogenic potential, life cycle and impact on the intensive production of fish.

Este trabalho tem por objetivo relatar a ocorrência de organismos semelhantes à Anaplasmataceae em monócitos de surubim híbridos. Durante a avaliação hematológica em peixes infectados por Pseudomonas sp., num evento natural, nos peixes cultivados no Estado de Mato Grosso do Sul, verificou-se a presença de várias inclusões pleomórficas, exibindo aparência rugosa e coloração predominantemente basofílica, apresentando-se em monócitos de apenas um indivíduo de surubim híbrido. Estas inclusões são similares aos corpúsculos elementares, corpos inicias e mórulas de bactérias pertencentes à família Anaplasmataceae. Estudos adicionais são necessários para caracterização molecular desta bactéria, bem como caracterização do potencial patogênico, ciclo de vida e impacto de sua ocorrência na produção intensiva de peixes e saúde pública.
Morphological identification of anaplasmataceae-like organisms in monocytes of the hybrid surubim catfish (Pseudoplatystoma reticulatum x P. corruscans) – case report
Keywords: Rickettsiales; fish bacteriosis; zoonosis